An investigation of character variation in Chaetobromus Nees (Danthonieae: Poaceae) in relation to taxonomic and ecological pattern - Verboom, George Anthony (Department of Biological Sciences, 2016)
Character variation in Chaetobromus, a genus of palatable grasses endemic to the arid western areas of southern Africa, was used to derive a classification reflecting taxonomic and ecological pattern. The present study differs from earlier biosystematic investigations by its much more intensive approach to sampling, with 75 anatomical, morphological and cytological characters and 169 individual samples being used. The use of larger population samples permitted quantification of variation within populations, in addition to that among populations and groups. Phenetic methods revealed the existence of three groups, approximating three formerly described taxa and reflecting divergent ecological strategies in Chaetobromus. A lack of diagnostic field characters argues against their recognition at species level, and Chaetobromus Nees is here described as monotypic, the type species, C. involucratus (Schrad.) Nees, comprising three subspecies C. involucratus subsp. involucratus, C. involucratus subsp. villosus Verboom and C. involucratus subsp. dregeanus (Nees) Verboom. There is overlap among subspecies in most characters although many showed significant mean differences. Within subspecies, character variation appears to be homogeneously distributed with respect to population boundaries suggesting that these are likely to have little impact on sampling. An investigation testing the effect of sample strategy on variation capture and taxonomic group detection suggests that a sample of 10-15 specimens is likely to account for most variation present. Phylogenetically, Chaetobromus is included in the tribe Danthonieae, and, on morphological evidence, is probably basal to a clade containing Pentaschistis, Pentameris and Pseudopentameris. The genus appears to occupy a niche unique among the African danthonioids, favouring lime-rich, basic soils and a strongly-seasonal winter-rainfall regime with arid summers. Ecological differences among the subspecies are reflected in differences in growth form and vegetative and reproductive phenologies. The niche requirements of Chaetobromus may be adequately specific to explain the patchy distribution of the genus. Bibliography: pages 119-131.